The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1140/epjds/s13688-016-0064-6
|View full text |Cite
|
Sign up to set email alerts
|

The Mobile Territorial Lab: a multilayered and dynamic view on parents’ daily lives

Abstract: The exploration of people's everyday life has long been of interest to social scientists. Recent years have witnessed a growing interest in analyzing human behavioral data generated by technology (e.g. mobile phones). To date, a few large-scale studies have been designed to measure human behaviors and interactions using multiple sources of data. A common characteristic of these studies is the population under investigation: students having similar daily routines and needs. This choice constraints the range of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 55 publications
(1 reference statement)
0
24
0
Order By: Relevance
“…Smartphones are increasingly used to study people's daily lives, tracking among others social interactions or mobility routines [10]. The largest bulk of studies using smartphones to collect data is to be found in health studies.…”
Section: Data Collection Via Smartphonesmentioning
confidence: 99%
“…Smartphones are increasingly used to study people's daily lives, tracking among others social interactions or mobility routines [10]. The largest bulk of studies using smartphones to collect data is to be found in health studies.…”
Section: Data Collection Via Smartphonesmentioning
confidence: 99%
“…The used dataset is part of the Mobile Territorial Lab [15]. However, symptoms and GPS tracks have not been released.…”
Section: Fundingmentioning
confidence: 99%
“…The study was conducted within the Mobile Territorial Lab ( http://www.mobileterritoriallab.eu ), a joint initiative created by Telecom Italia, Fondazione Bruno Kessler, MIT Media Lab and Telefonica [ 54 ]. Following the Italian regulations, all participants were asked to sign an informed consent form and the study was conducted in accordance to it.…”
Section: Methodsmentioning
confidence: 99%